METHODOLOGY OF STUDY OF GRAIN SUB-COMPLEX DURING GLOBALIZATION - O. V. Sidorenko (Зерновое хозяйство России, 2018)
Development of domestic grain sub-complex in the conditions of Russia's membership in the World Trade Organization (WTO), the Customs Union, the adoption of an agreement on free trade zone of the Eurasian Economic Community, is functioning in the context of tightening international competition and integration. At the same time the problem of balance of functionally industrial areas and agricultural industries, the problem of optimization of their economic cooperation, the problem of technological modernization in the field of storage, processing and transporting, the problem of improvement of the efficiency and stability of grain production, the problem of ensuring of the competitiveness of grain and its processed products in foreign and domestic markets still remain unsolved. Consideration of these and other issues makes the claimed scientific field especially urgent. The aim of the study is substantiation of methodological principles of grain sub-complex development during a globalization period.  In the paper the principle positions of the functioning of grain sub-complex today have been clarified using scientific methods of research. We have determined the factors which influence on its formation and development. Assessment criteria, functions and peculiarities have been presented here. We have made a conclusion that development of agro-industrial units should meet the requirements of stability, efficiency and competitiveness. The functional-branch structure, the diagram and the algorithm of research of grain sub-complex have been developed. Theoretical and practical significance of the results is that they can serve as a basis for further development of the research methodology of grain sub-complex and substantiation of conceptual approaches to the evaluation of its development. They can allow participating in the development of promising proposals for improving the formation and implementation of the national grain policy in the context of the major priorities of the development of the Russian agricultural sector.